Catalytic Asymmetric Epoxidation of Aldehydes with Two VANOL‐Derived Chiral Borate Catalysts. Issue 11 (7th February 2019) - Gupta, Anil K.; Yin, Xiaopeng; Mukherjee, Munmun; Desai, Aman A.; Mohammadlou, Aliakbar; Jurewicz, Kelsee; Wulff, William D.
Abstract: A highly diastereo‐ and enantioselective method for the epoxidation of aldehydes with α‐diazoacetamides has been developed with two different borate ester catalysts of VANOL. Both catalytic systems are general for aromatic, aliphatic, and acetylenic aldehydes, giving high yields and inductions for nearly all cases. One borate ester catalyst has two molecules of VANOL and the other only one VANOL. Catalysts generated from BINOL and VAPOL are ineffective catalysts. An application is shown for access to the side‐chain of taxol. Abstract : A tale of two catalysts : Two different borate catalysts for the epoxidation of aldehydes with diazoacetamides can be generated from boron and VANOL (3, 3′‐diphenyl‐2, 2′‐bi‐1‐naphthalol). That these catalysts are different is demonstrated by a nonlinear study on the relationship of the enantiopurity of the product epoxide versus that of VANOL. Despite their structural differences, both catalysts display a similar substrate scope profile with excellent asymmetric induction for various aldehydes.